Financial Poverty in Developed Countries: The Evidence from LIS: Final Report to the UNDP - Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1997)
The object of this report is to review the available evidence on the extent and nature of financial poverty in modern rich nations within the OECD and selected other nations. While there is discussion of broader concepts of poverty such as those related to deficits in capabilities, social exclusion, violence and insecurity, the main concern is with financial poverty as measured by annual after-tax disposable income. Both absolute and relative poverty measures are presented and attempts are made to link the types of poverty standards used in rich nations to those used in developing nations. This paper served as the basis for all OECD country poverty rates as reported in the United Nations' 1997 Human Development Report, which was released on June 12, 1997.
Keywords: 330; Armut; Steuerbelastung; Welt